Arthur C. Danto: Between analytical philosophy of history and substantive philosophy of history - Camargo Flórez, Martín Alonso (Estudios de Filosofía, 2007)
Danto’s Analytical Philosophy of History tries to solve the problem of the logical limit of History based on the elaboration of the narrative sentence. The said solution implies the rejection of any type of Substantive Philosophy of History because of its theoretical compromise with Narrative Realism and the transgression of the limits of historical language. Nonetheless, with his Philosophy of Art he has guaranteed the validity of Substantive Philosophy of History, so he can understand the narrative sentence from the point of view of Narrative Realism based on the difference between History and story.